1997
DOI: 10.1002/hep.510250134
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Intraoperative Biopsies and Liver Function Tests for Preservation Injury in Orthotopic Liver Transplantation

Abstract: and ALT values are not useful in the assessment of PI. Eighty liver allografts were studied to determine the (HEPATOLOGY 1997;25:184-189 .) predictive value of intraoperative biopsies and postoperative liver function tests for the development of preservation injury (PI). Peak transaminase (aspartate transaminase [AST] and alanine transaminase [ALT])Graft viability is of the utmost importance for successful and prothrombin time (PT) values achieved by each pa-orthotopic liver transplantation. Virtually all live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…Although the results in the 20 patients reported here showed no statistical difference in the primary outcome, with an important caveat regarding the small numbers, it suggests that NMP halves peak transaminase, a surrogate marker for graft function (20,21) and preservation injury (22,23). As noted above, the control group covered a longer time period than the intervention group to allow adequately matched control patients to be identified in the two liver transplant units concerned.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although the results in the 20 patients reported here showed no statistical difference in the primary outcome, with an important caveat regarding the small numbers, it suggests that NMP halves peak transaminase, a surrogate marker for graft function (20,21) and preservation injury (22,23). As noted above, the control group covered a longer time period than the intervention group to allow adequately matched control patients to be identified in the two liver transplant units concerned.…”
Section: Discussionmentioning
confidence: 61%
“…Matched control patients were identified as described above; to find two matched controls, preset criteria were extended in some cases, MELD was 12 in NMP versus 14 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) in matched controls (p = 0.55).…”
Section: Donor and Recipient Characteristicsmentioning
confidence: 99%
“…The severity of hepatocellular necrosis was graded as follows: 0, no necrosis; 1, focal necrosis with individual acidophilic cells; 2, confluent necrosis involving 2 to 3 adjacent hepatocytes; and 3, zonal necrosis with large areas of confluent necrosis involving the entire lobule. 2 Macrovesicular and microvesicular steatosis were judged as follows: mild, fat present in less than 30% of hepatocytes; moderate, fat infiltration of 31% to 60%; and severe, fat infiltration greater than 61% of hepatocytes. The presence of fibrotic bridges, cholestatic changes, sinusoidal dilatation, and glucogenized nuclei was also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have analyzed the predictive value of postreperfusion liver biopsies for the development of graft dysfunction and late complications. Kakizoe et al 1 and Gaffey et al 2 showed that necrosis and neutrophilic inflammation in intraoperative postreperfusion biopsy specimen were predictive of graft initial poor function (IPF). Other studies have shown that sinusoidal cells are damaged during cold ischemia time, and warm ischemiainjures endothelial cells.…”
Section: Biliary Complications After Orthotopic Liver Transplantationmentioning
confidence: 99%
“…However, there is scarce information about GSH and GSSG liver concentrations after cold storage and reperfusion in clinical OLT. Moreover, only few reports have correlated donor risk factors with histopathological reperfusion injury found in the liver tissue 7,8 . The objectives were to evaluate GSH and GSSG liver concentrations after cold storage and reperfusion in optimal and suboptimal grafts and also the initial histopathological injury and function of the grafts.…”
Section: Introductionmentioning
confidence: 99%